Biodegradable unsaturated polyesters containing2, 3-butanediol for engineering applications: Synthesis, characterization and performances. (10th February 2016) - Hu, Xiaoran; Shen, Xiaolin; Huang, Mengfei; Liu, Chaohao; Geng, Yiting; Wang, Runguo; Xu, Riwei; Qiao, He; Zhang, Liqun
Abstract: Highly purified 2, 3-butanediol (2, 3-BDO) was obtained from glycerol by using metabolically engineered Escherichia coli through biosynthetic pathways. The bio-elastomers with high strength and elasticity was then prepared from the synthetic 2, 3-butanediol and several commercially renewable monomers as promising materials for engineering applications. The molecular weights, chemical structures, and thermal transitions of the bio-elastomers were confirmed by GPC, NMR, FTIR, TGA, DSC and WAXD. Importantly, the introduction of 2, 3-BDO can limit and even prevent the crystallization of these bio-elastomers, which makes them amorphous and ensure their high elasticity. Furthermore, the bio-elastomers were highly reinforced with nanosilica which can meet the requirements for the majority of rubber products. Results of in vitro degradation tests prove these bio-elastomers can adjust the degradation rate of their composites by crosslinking. Cell adhesion and proliferation were adopted to evaluate the potential biocompatibility of SiO2 /PBPSSI composites and the results indicated that all the SiO2 /PBPSSI composites were essentially noncytotoxic. In general, the petroleum-independent monomers, relatively simple synthesis and adjustable degradation rate could greatly reduce environmental impact and the fine mechanical properties and excellent biocompatibility make these novel synthetic bio-elastomers sustainable materials for engineering applications. Graphical abstract: Highlights: Based on microbial production of 2, 3-butanediol in our laboratory, we synthesized linear and crosslinkable bio-elastomers. The introduction of 2, 3-butanediol can highly suppress the crystallization of bio-elastomers and makes them fully amorphous. These bio-elastomers can be effectively reinforced by nanosilica and their degradation rate can be adjusted by crosslinking. Good performances of bio-elastomers make them environment-friendly and potential candidates for engineering applications.